2007
DOI: 10.1007/s00027-006-0823-8
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal scales of transport during the cooling phase of the ice-free period in a small high-mountain lake

Abstract: We examine, by means of scaling analysis tools and three-dimensional numerical simulations, the time and spatial scales of transport and mixing processes during the cooling phase of the ice-free period in La Caldera, a small lake located at 3,050 m.a.s.l. in Sierra Nevada (Southern Spain). La Caldera is used here as a prototypical example of small high-mountain lakes. Our results demonstrate that transport and mixing in small highmountain lakes are shaped by the severe changes exhibited at diurnal time scales … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 35 publications
0
25
0
Order By: Relevance
“…On the contrary, DT sa over Ngoring Lake increased from late AIRÁLAKE BOUNDARY LAYER AND LAKE SCHEME PERFORMANCE OVER TIBETAN PLATEAU spring to late autumn, following the seasonal pattern similar to that of low-altitude temperate lakes (Kirillin, 2010), but different from tropical lakes (Verburg and Antenucci, 2010). Apart from the TP, a similar unstable temperature difference pattern was observed over alpine lake La Caldera (378N, 3.38W, 3050 m asl) from early July to August (Rueda et al, 2007), suggesting the boundary layer instability to be a common phenomenon for high-altitude lakes. The SLCLM demonstrated good performance for high-altitude lakes, although originally developed based on low-altitude lakes.…”
Section: Discussionmentioning
confidence: 71%
“…On the contrary, DT sa over Ngoring Lake increased from late AIRÁLAKE BOUNDARY LAYER AND LAKE SCHEME PERFORMANCE OVER TIBETAN PLATEAU spring to late autumn, following the seasonal pattern similar to that of low-altitude temperate lakes (Kirillin, 2010), but different from tropical lakes (Verburg and Antenucci, 2010). Apart from the TP, a similar unstable temperature difference pattern was observed over alpine lake La Caldera (378N, 3.38W, 3050 m asl) from early July to August (Rueda et al, 2007), suggesting the boundary layer instability to be a common phenomenon for high-altitude lakes. The SLCLM demonstrated good performance for high-altitude lakes, although originally developed based on low-altitude lakes.…”
Section: Discussionmentioning
confidence: 71%
“…Unstable ABL conditions have been shown to persist above lakes for long periods [ Rouse et al ., ], resulting in enhanced turbulent heat loss. ABL conditions have been reported in lake studies from around the world, in tropical [ Verburg and Antenucci , ] and temperate regions [ Derecki , ; Lofgren and Zhu , ; Laird and Kristovich , ; Rueda et al ., ] but no study has compared ABL stability across a range of latitudes and other lake attributes.…”
Section: Introductionmentioning
confidence: 99%
“…We predicted that absolute latitude, which is strongly related to annual mean air temperature and net radiation, would have a strong influence on lake temperature (Straskraba 1980;Piccolroaz et al 2013) and thus heat fluxes at the air-water interface. Altitude can influence air-water temperature relationships via differential lapse rates (Livingstone et al 1999), and we thus predicted it would influence the cooling fluxes (Rueda et al 2007;Verburg and Antenucci 2010). We predicted that lake area would be an important predictor of surface energy fluxes given that it regulates surface temperature at diel timescales (Woolway et al 2016) and thereby surface cooling in lakes and has also been shown as an important predictor of the relative importance of convective vs. wind-driven mixing (Read et al 2012).…”
mentioning
confidence: 97%